PENGARUH MANAJEMEN GREEN WAKAF DALAM PROGRAM GREENHOUSE MELON HIDROPONIK "STUDI KASUS : PROGRAM DI DAERAH PURWOJATI LAZIZMU BANYUMAS" - Anwar Hanifudin; Galih Setiadi; Trehandyan Bena Pradipa; Mahardhika Cipta Raharja (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study analyzes the influence of Green Waqf management on the success of the hydroponic melon greenhouse program in the Purwojati area, managed by LAZISMU Banyumas. This is due to the problem of low agricultural productivity due to dependence on conventional climates and limited capital for local farmers. Using qualitative methods with a library research approach, secondary data was processed through financial feasibility analysis “Revenue Cost Ratio” and literature synthesis to measure the impact of waqf management variables on production efficiency. The results show that the integration of Green Waqf instruments significantly mitigates the high investment risk in hydroponic technology. Standardized productive asset management has been shown to increase the cropping index by up threefold within a year and stabilize farmer incomes. A discussion of the literature confirms that through professional waqf governance, this program is able to support the sustainability of productive agricultural activities while increasing the economic capacity of the beneficiary communities. The program also has the potential to encourage the economic transformation of the community towards better independence through the productive and sustainable management of waqf assets.